Ambiguity - Jürgen Eichberger; David Kelsey (University of Heidelberg, Department of Economics, 2007)
Ambiguity refers to a decision situation under uncertainty when there is incomplete information about the likelihood of events. Different formal models of this notion have been developed with differing implications about the representation of ambiguity and ambiguity aversion.
Keywords: D81; 330; uncertainty; ambiguity; ambiguity attitude; Entscheidung unter Unsicherheit; Risikoaversion; Theorie